474 - Special considerations for lithium use in Older Age Bipolar Disorder. (October 2020) - Mangas, Mariana Duarte; Pedro, Catarina; Jorge, Beatriz
Abstract : Lithium is the oldest and still one of the most frequently prescribed mood stabilizers in the treatment of bipolar disorder. Though, the implications of lithium use in the older population remain less understood. This work aims to provide an understanding of the impact of lithium in older age bipolar disorder, including tolerability and efficacy. A non-systematic review was performed on PubMed database, using the key words "lithium older adult bipolar disorder" and references from recent international bipolar disorder guidelines. There is an evidence base that lithium is effective in older age bipolar disorder. Aging-associated pharmacokinetic and pharmacodynamic changes as well as increased rates of medical comorbidities and polypharmacy predispose older patients to a higher risk of lithium toxicity. Careful monitoring and adjustment of lithium dosage is especially important in older adults to minimize the risk of toxicity.